Anthropometric and physiological characteristics of male soccer players according to their competitive level, playing position and age group: a systematic review - Slimani, M.; Nikolaidis, P. T. (The Journal of Sports Medicine and Physical Fitness, 2019)
INTRODUCTION: The aim of the present systematic review was to profile soccer players` anthropometric, physiological, and physical attributes relative to different competitive levels, playing positions and age groups. EVIDENCE ACQUISITION: The systematic search was conducted using different databases and according to the Population/Intervention or Exposure/Comparison/Outcome(s) [PICO] criteria. EVIDENCE SYNTHESIS: The present review shows that the somatotype characteristics, percentage (%) of body fat, maximal oxygen uptake (VO2max), repeated-sprint ability (RSA), running speed, strength, and muscular power of the lower limbs were the most powerful discriminators between male soccer players of different competitive levels, playing positions, and age groups. Specifically, higher VO2max, muscle strength, muscular power (vertical jump height), running speed (10-30 m) and agility, and lower % of body fat were identified in elite soccer players (higher-level) compared to all other competitive levels (i.e., lower-level: sub-elite, amateur, recreational). As for the competitive level differences, higher VO2max, mean anaerobic power, RSA and sprint performances (5 to 20 m), and lower % of body fat and lower limbs` explosive capabilities (countermovement jump [CMJ] and squat jump [SJ]) were found in outfielders (forwards, midfielders, and defenders) as compared to goalkeepers, from a very youth age (8 years old). Concerning age-related performance, it appears that physical performance increased significantly with age. CONCLUSIONS: These data, together with the fact that each position, age category, and playing level has a different physiological background in male soccer players, demonstrate that training programs should be individualized to each position, playing level and age category, as is already done with goalkeepers.